1984
DOI: 10.1161/01.cir.70.3.485
|View full text |Cite
|
Sign up to set email alerts
|

Low zero-flow pressure and minimal capacitance effect on diastolic coronary arterial pressure-flow relationships during maximum vasodilation in swine.

Abstract: During maximum dilation with adenosine in dogs, the diastolic coronary pressure at which flow ceases (Pzf) has been observed to be up to 27 mm Hg above coronary sinus and right atrial pressures. We studied swine to measure the Pzf and to determine the effects of interventions that change collateral flow and coronary capacitance. In 44 swine, the left anterior descending coronary artery (LAD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 42 publications
5
21
1
Order By: Relevance
“…Our findings, as summarized in the Table, corroborate the findings of Pantely et al 10,12 relating to the hemodynamic stability of instantaneous hyperemic end-diastolic measurements. This is evident in minimal fluctuations in coronary resistance and wedge pressure despite substantially reduced impedance to coronary blood flow, as opposed to full-cardiac cycle measurements that include the effects of systole.…”
Section: Comparison With Other Studiessupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings, as summarized in the Table, corroborate the findings of Pantely et al 10,12 relating to the hemodynamic stability of instantaneous hyperemic end-diastolic measurements. This is evident in minimal fluctuations in coronary resistance and wedge pressure despite substantially reduced impedance to coronary blood flow, as opposed to full-cardiac cycle measurements that include the effects of systole.…”
Section: Comparison With Other Studiessupporting
confidence: 92%
“…For end-diastolic FFR, the same 3 cardiac cycles were analyzed, respectively, except that instantaneous values at 60 ms before R-wave of the ECG were averaged. This was a slightly modified technique from a large animal study by Pantely et al 10 who also sampled the end-diastolic phase 60 ms before onset of the QRS complex of the ECG. We chose the R-wave to simplify and automate ECG-gating.…”
Section: Coronary Pressure and Flow Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, support comes also from studies in swine which normally have very little collateral coronary flow (Fedor et al, 1978;Millard, 1980;Sjoquist et al, 1984). If our hypothesis about the influence of collateral flow on pressure axis intercept is correct, there should be little difference between pressure axis intercepts or peripheral coronary pressures in the left main coronary artery or in one of its branches in swine; Bellamy and O'Benar (1984) noted that flow stopped at a left main coronary arterial pressure of 13 ± 5 mm Hg, whereas Pantely et al (1984) observed a pressure axis intercept of 12.1 ± 3.1 mm Hg in the left anterior descending coronary artery.…”
Section: Effects Of Interarterial Pressure Gradientsmentioning
confidence: 83%